2011
DOI: 10.1021/mp200392g
|View full text |Cite
|
Sign up to set email alerts
|

A Single Sublingual Dose of an Adenovirus-Based Vaccine Protects against Lethal Ebola Challenge in Mice and Guinea Pigs

Abstract: Sublingual (SL) delivery, a non-invasive immunization method that bypasses the intestinal tract for direct entry into the circulation, was evaluated with an adenovirus (Ad5)-based vaccine for Ebola. Mice and Guinea pigs were immunized via the intramuscular (IM), nasal (IN), oral (PO) and SL routes. SL immunization elicited strong transgene expression in and attracted CD11c(+) antigen presenting cells to the mucosa. A SL dose of 1 × 108 infectious particles induced Ebola Zaire glycoprotein (ZGP)-specific IFN-γ+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…Sublingual administration of an adenovirus (Ad5)-based Ebola vaccine protected more mice with pre-existing immunity to Ad5 than intramuscular injection[76]. Pulmonary aerosol vaccination in rats with a viral-like particle(VLP)-based vaccine targeting the HIV co-receptor, CCR5, could elicit, not only vaccine-specific IgG and IgA antibodies in serum, but also IgA antibodies at local mucosal sites, while intramuscular vaccination could only induce serum IgG and IgA antibody responses[77].…”
Section: Introductionmentioning
confidence: 99%
“…Sublingual administration of an adenovirus (Ad5)-based Ebola vaccine protected more mice with pre-existing immunity to Ad5 than intramuscular injection[76]. Pulmonary aerosol vaccination in rats with a viral-like particle(VLP)-based vaccine targeting the HIV co-receptor, CCR5, could elicit, not only vaccine-specific IgG and IgA antibodies in serum, but also IgA antibodies at local mucosal sites, while intramuscular vaccination could only induce serum IgG and IgA antibody responses[77].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental infections of rodents and NHPs it was demonstrated that pre-existing immunity significantly lowered protective efficacy of rAd5-based vaccines [35, 3842]; however, improvements to the immunization route or the vaccine vector itself have been used to overcome this problem. For instance, delivery of the vaccine via the oral, nasal or intratracheal route can circumvent pre-existing immunity without having an effect on the protective efficacy against lethal challenge; in addition, the stimulation of T cell responses was significantly improved [35, 3941]. These efforts have been pushed further by replacing the rAd5 vector with a different serotype-based backbone with less or no pre-existing immunity in humans like Ad26 and Ad35 [42] or to primate-specific adenoviruses such as chimpanzee (Ch)Ad and simian Ad21 [38, 43].…”
Section: Non-replicating Vaccine Vectorsmentioning
confidence: 99%
“…In experimental infections of rodents and NHPs, it was demonstrated that pre-existing immunity significantly lowered protective efficacy of Ad5-based vaccines [33,3539], and scientist have started to improve the immunization route or the vaccine vector itself to overcome this problem. It could be demonstrated that delivery of the vaccine via the oral, nasal or intratracheal route can circumvent pre-existing immunity without affecting the protective efficacy against lethal challenge; in addition, the stimulation of T cell responses was significantly improved [33,36,37,39]. Furthermore, administration of a boosting vaccine dose has been shown to overcome the presence of rAd5-specific immunity in NHPs [40].…”
Section: Nonreplicating Vaccine Vectorsmentioning
confidence: 99%